2018
DOI: 10.17352/2455-5363.000018
|View full text |Cite
|
Sign up to set email alerts
|

Meta-Analysis of Risk Factors for Development of Liver Cirrhosis in Chronic Hepatitis B Patients

Abstract: Chronic hepatitis B virus (HBV) infection and chronic hepatitis C virus (HCV) are main reasons for the development of liver cirrhosis (LC) on a worldwide scale. Chronic HBV infection is a main reason for the development of LC in high-risk areas, for example, China and Africa, whereas chronic HCV infection is a main reason in developed countries. In China, the harm of LC is serious, and 30 million of chronic hepatitis B (CHB) patients is the major source of LC and the one-year cumulative incidence rate of LC in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…34,41 This can be explained by a meta-analysis study by Cai et al who found that age, ratio of AST, and ALT were other influential factors causing liver fibrosis in chronic hepatitis B patients in addition to other factors such as male sex, family history of hepatitis B, increased duration of hepatitis B, alcohol drinking habit, smoking, and increased total bilirubin levels. 53 A study by Yang YT et al reported that platelet count can be used as a marker of the severity of liver injury and liver fibrosis in chronic hepatitis B infection. 54 In patients with advanced liver disease and decompensated cirrhosis, low serum albumin is caused by impaired liver function and albumin synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…34,41 This can be explained by a meta-analysis study by Cai et al who found that age, ratio of AST, and ALT were other influential factors causing liver fibrosis in chronic hepatitis B patients in addition to other factors such as male sex, family history of hepatitis B, increased duration of hepatitis B, alcohol drinking habit, smoking, and increased total bilirubin levels. 53 A study by Yang YT et al reported that platelet count can be used as a marker of the severity of liver injury and liver fibrosis in chronic hepatitis B infection. 54 In patients with advanced liver disease and decompensated cirrhosis, low serum albumin is caused by impaired liver function and albumin synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…Second, previous studies and most of the reported noninvasive models were based on viral or liver factors, such as aspartate aminotransferase/alanine aminotransferase (AST/ALT) ratio, HBV DNA viral load, HCV RNA load, AST-to-platelet ratio index, and platelet count (19)(20)(21)(22)(23)(24). However, data are limited for the noninvasive models based on the host factors, which are also related with liver cirrhosis (25). The viral or liver indices could only be obtained by laboratory testing; the results were not immediately available for patients, and the cost also led to limited availability, especially in resource-limited settings (26).…”
Section: Introductionmentioning
confidence: 99%